Unmasking atypical dengue: a case of multi-organ failure and acute coronary syndrome - Naved, Saad Ahmed; Ghazia Hussain; Shamona Arshad; Naveed Latif; Muhammad Ashraf (Journal of the Pakistan Medical Association, 2026)
This case report discusses a rare and challenging presentation of dengue haemorrhagic fever (DHF) in a 62-year-old male, complicated by acute coronary syndrome (ACS) and multi-organ failure (MOF). The patient was initially afebrile, presented with respiratory symptoms, and was diagnosed with non-ST elevation myocardial infarction (NSTEMI) and cardiogenic shock. Dengue serology confirmed a secondary dengue infection with profound thrombocytopenia, respiratory failure, and cardiogenic shock. Coronary angiography revealed triple-vessel disease, prompting consideration of coronary artery bypass grafting (CABG). However, owing to severe dengue-related complications, a multidisciplinary team deferred surgery in favour of medical management, leading to gradual haemodynamic recovery. This case underscores the importance of recognising atypical dengue presentations, especially in endemic regions, and highlights the complex interplay between dengue and pre-existing coronary artery disease in acute coronary syndrome (ACS). Prompt diagnosis, multidisciplinary collaboration, and individualised management are crucial for improving the outcomes in severe dengue cases with cardiac involvement. Keywords: Dengue haemorrhagic fever, Acute coronary syndrome, Multi-organ failure, Cardiogenic shock, Thrombocytopenia, Coronary artery disease, Multidisciplinary management.